Gold catalysis: products and intermediates obtained from N-propargylcarboxamides bearing additional substituents on nitrogen - Hashmi, A. Stephen K.; Molinari, Lise; Rominger, Frank; Oeser, Thomas (European journal of organic chemistry, 2011)
The reaction of several propargylamide substrates with additional substituents on the nitrogen atom was investigated. Under aqueous conditions acyloxy-substituted allylammonium salts could selectively be obtained. Monitoring of the reactions by 1H NMR spectroscopy indicated the presence of an intermediate. Then switching to anhydrous reaction conditions allowed the isolation and characterization of these intermediates, oxazoliniminium species. Workup of the allylammonium salts under basic conditions led to an acyl transfer from the oxygen atom to the nitrogen atom, which proves that these products are not formed by a direct gold-catalysed hydration of the triple bond only, and at the same time nicely explains the selective monohydration of only one out of two triple bonds.
Gesehen am 07.09.2022